2023
DOI: 10.1186/s13073-023-01166-7
|View full text |Cite
|
Sign up to set email alerts
|

Automated prioritization of sick newborns for whole genome sequencing using clinical natural language processing and machine learning

Abstract: Background Rapidly and efficiently identifying critically ill infants for whole genome sequencing (WGS) is a costly and challenging task currently performed by scarce, highly trained experts and is a major bottleneck for application of WGS in the NICU. There is a dire need for automated means to prioritize patients for WGS. Methods Institutional databases of electronic health records (EHRs) are logical starting points for identifying patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…If this gap is not overcome, it will further deepen the inequities in access to NBS between different regions worldwide. Genetic studies are essential for the adequate diagnosis, management (i.e., selection of patients for specific treatment), and prognosis of IEiM patients, especially in the pediatric population and even more so in critically ill patients, allowing personalized medicine approaches [ 67 , 68 ]. These studies are also helpful for the establishment of the prognosis of those cases of MAA where different forms (mut 0 and mut - ) of the disease differently impact the patient survival [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…If this gap is not overcome, it will further deepen the inequities in access to NBS between different regions worldwide. Genetic studies are essential for the adequate diagnosis, management (i.e., selection of patients for specific treatment), and prognosis of IEiM patients, especially in the pediatric population and even more so in critically ill patients, allowing personalized medicine approaches [ 67 , 68 ]. These studies are also helpful for the establishment of the prognosis of those cases of MAA where different forms (mut 0 and mut - ) of the disease differently impact the patient survival [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Kingsmore et al . (31) showed that more HPO terms may not increase diagnostic yield, but that a more focused list of key terms may support analysis more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, AI can be used to automate the identification of patients who are likely to benefit from URGS, RGS, or RES. Machine learning, together with NLP of the EHR, has been used to develop classifiers that distinguish between NICU infants who have or have not historically received URGS, RGS, or RES 166 . As URGS, RGS, and RES are implemented in NICUs without prior experience, such tools will be important in achievement of high diagnostic rates.…”
Section: Increasing Use Of Artificial Intelligence (Ai) In Urgsmentioning
confidence: 99%